Methodology strategy manual aviation gas turbine engines for the technical condition controls the level of airworthiness - Чоха, Ю.М. (Proceedings of National Aviation University (archive), 2006)
Offered methodology to conceptual new strategy to usages aircraft gas turbine engine with use criterion level available